EKSPLORASI POTENSI SENYAWA BIOAKTIF MAKROALGA LAUT Sargassum sp ASAL PESISIR ACEH BARAT SEBAGAI AGEN ANTIOKSIDAN - Mohamad Gazali; Neviaty Zamani; Nurjanah Nurjanah; Zulfadhli Zulfadhli; Eri Safutra (Journal of Aceh Aquatic Sciences, 2017)
Marine Macroalgae Sargassum sp is a one of macroalgae species that develop rapidly and distributed widely in the South-West Coastal of Aceh. However, marine macroalgae has not yet utilized optimally by Aceh’s community especially comercial product that give value added. This research was conducted by using marine macroalgae Sargassum sp that derived from West Aceh coastal. The measurement of antioxidant activity was undertaken by using CUPRAC (cupric ion reducing antioxidant capacity) method. The aim of this research is to explore bioactive compound to marine macroalgae Sargassum sp as antioxidant. Sargassum sp is a brown algae that generally attached in dead coral substrate or rocky intertidal zone that influenced by low tide. The result of measurement of antioxindat activity is 180,535 µmol troloks/g dried powder. Thi is suspected that hidrocinamate acid is polyfenol groups that role as antioxidant substance becauce it possess hyrodgen atom from functional hydroxyl groups that contributed by free radical.Keywords : Macroalgae, Sargasssum sp, Antioxidant, West Aceh